Assessing socio-ecological factors on caesarean section and vaginal delivery: an extended perspective among women of South-Punjab, Pakistan - Muhammad Muneeb Hassan; Muhammad Ameeq; Laraib Fatima; Sidra Naz; Sheikh Muhammad Sikandar; Alpha Kargbo; Shabana Abbas (Taylor & Francis Group, 2023)
Research was conducted employing the extended socio-ecological model (ESEM) to examine factors associated with cesarean sections (CSs) and vaginal deliveries (VDs) among the women in our study population. Using the ESEM to determine South-Punjab and Pakistani women's mode of delivery predictors. The cross-sectional study with a sample size of 908 patients was conducted through private and public obstetrics and gynecology departments in South Punjab, Pakistan, from 12 June 2022 to 29 May 2023. The Chi-square analysis compared baseline variables, delivery outcomes and delivery methods. Logistic regression analysis is used to determine predictive factors. The study revealed that 75.66% of women had CS, while 24.34% had VD. Education level, age, residential area and fetal presentation all had significant associations with mode of delivery. Logistic regression analysis suggested that gynecologist recommendation, belief in CS safety, abnormal fetal presentation, maternal anemia and meconium aspiration syndrome were all significant predictors of CS. The ESEM model concluded that age, fatigue and women's preference for CS due to its reliability for her and her fetus were predictive factors for mode of delivery choices among South-Punjab Pakistani women.